2019
DOI: 10.1515/applirev-2018-0106
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of individual differences in aural vocabulary knowledge, written vocabulary knowledge and working memory capacity on explaining L2 learners’ listening comprehension

Abstract: Listening comprehension constitutes a considerable challenge for second language learners, but little is known about the relative contribution of individual differences in distinct factors to listening comprehension. Since research in this area is relatively limited in comparison to that focusing on the relationship between reading comprehension and factors such as vocabulary knowledge and working memory, there is a need for studies that seek to fill the gap in our knowledge about the specific contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 48 publications
8
42
0
Order By: Relevance
“…One interesting finding of the current study is the lack of a role for WM and LA in L2 listening skills. Although a number of studies have shown a significant relationship between WM and L2 listening comprehension (e.g., Brunfaut & Révész, 2015;Gu & Wang, 2007;Masrai, 2020), our findings corroborate those studies that reported a lack of a significant relationship (Andringa et al, 2012;Vandergrift & Baker 2015, 2018. Almost all of these studies demonstrated that linguistic knowledge was the strongest predictor of L2 listening comprehension, while the contribution of WM beyond linguistic knowledge was inconclusive.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One interesting finding of the current study is the lack of a role for WM and LA in L2 listening skills. Although a number of studies have shown a significant relationship between WM and L2 listening comprehension (e.g., Brunfaut & Révész, 2015;Gu & Wang, 2007;Masrai, 2020), our findings corroborate those studies that reported a lack of a significant relationship (Andringa et al, 2012;Vandergrift & Baker 2015, 2018. Almost all of these studies demonstrated that linguistic knowledge was the strongest predictor of L2 listening comprehension, while the contribution of WM beyond linguistic knowledge was inconclusive.…”
Section: Discussionsupporting
confidence: 88%
“…Vandergrift andBaker (2015, 2018) also reported that, although WM correlated significantly with L2 listening in the initial stages of analysis, the findings revealed lack of significant contribution of WM to listening comprehension in grade four and seven French immersion learners. On the other hand, a very recent study (Masrai, 2020) conducted with 130 B-2 level (i.e., upper intermediate according to the Common European Framework of Reference, 2001) students at a university reported that WM was a significant predictor of L2 listening comprehension measured through the IELTS. Masrai (2020) reported that WM explained an additional 14% of the variance in L2 listening skill in addition to vocabulary knowledge.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…As most of the previous studies have been survey based, and focused mainly on the students' preferences over the available learning strategies, but never focused on their actual level as per their academic achievements. The results of this study revealed that all strategies are helpful depending on the content, context, and on the nature of exposure of the students, it depends on the teachers to make use of all strategies to better suit the learners' needs and proficiency level (Ma, 2009;Masrai, 2019;Al-Masrai & Milton, 2012;Ishtiaq et al, 2017;Mohammad & Hazarika, 2016. Ma's (2009 process-oriented vocabulary learning strategies also proposes the stages of acquisition and for each stage learners make use of four strategies (cognitive, metacognitive, social and affective) as per their needs.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that poor reading skills of Saudi L2 learners attributed to limited vocabulary (AL-Qahtani, 2016). Moreover, recently Masrai (2019) found that there was a strong correlation between vocabulary acquisition and listening skills of Saudi L2 learners (Masrai, 2019). Undoubtedly, acquiring new vocabulary is a major hurdle for ESL/EFL learners in developing proficiency (Huckin, Haynes, & Coady, 1993).…”
Section: Introductionmentioning
confidence: 99%